A framework for exploring and managing biocultural heritage. (March 2019) - Lindholm, Karl-Johan; Ekblom, Anneli
Abstract: The conceptual framework of biocultural heritage allows for new approaches to heritage, nature conservation, landscape planning and development goals, providing means to negotiate management goals in these areas, and in certain cases, also to combine them. By reviewing knowledge from the literature, this paper develops a new conceptual framework of biocultural heritage. Five "elements" constitute biocultural heritage in this framework. First, ecosystem memories denote biophysical properties, non-human organisms and agents changed or affected directly or indirectly by humans. Second, landscape memories represent tangible materialised human practice and semi-intangible ways of organising landscapes, such as built environments and archaeological sites, and settlement systems linked to user and property rights. Third, place-based memories refer to intangible living features of human knowledge and communication expressed in know-how, place names, orature, arts, ideas and culture, received, preserved and transmitted over generations. The fourth element, integrated landscape analysis, denotes a toolbox and a conceptual framework for knowledge construction and landscape management. The final fifth element of biocultural heritage, stewardship and change, represents the activity of, and ability in, exploring memory reservoirs of biocultural heritage for transferring knowledge to policy and management and for shaping collaborative initiatives. To illustrate the framework, this paper then presents a study from the village Ängersjö located in the boreal forest in central Sweden. As conclusion, we suggest that the approach - with improvements and modifications - represents an operational joint framework for exploring and managing biocultural heritage, drawing on the past for envisioning the future.